Bantayog discovering Manila through its monuments - Capili, Maria Angelica A.; Osias, Jarie R.; Flores, Ferdinand P.; Baguio, Bryan Jess T.; Suliguin, Geronimo C. Jr.; Villanueva, Rogelio E. Jr.; Goce, Rona Beth G.; Velasco, Zoilo A.; Borra, Alena Grace S.; Beup, Fernando V.; Flores, Shirley L.; Garcia, Michael Lyndon B.; et al. (Metro Manila Foreign Service Institute, Department of Foreign Affairs, 2008)
History of Manila through the different monuments all over the city.
Profiles of 33 Filipinos to whom monuments in Manila are dedicated.
Includes bibliographical references (pages 70-77).
Keywords: Manila (Philippines) -- History; Manila (Philippines) -- Pictorial works